QSAR Analysis of Aminoquinoline Analogues as MCH1 Receptor Antagonist - Patel, D. K.; Patel, N. M. (Journal of Scientific Research, 2009)
Quantitative structure activity relationship (QSAR) has been established for 2-aminoquinoline-6-carboxamide melanin-concentrating hormone (MCH) 1R antagonists. The multiple linear regressions were used to generate the relationship between biological activity and calculated descriptors. From the 100 of models with r2 > 0.700 was developed. Final selected model was prepared using four descriptors (DMXC, KChiV4, Rcom, and IM1L) which are belong to topological, steric, spatial and electrotopological class descriptor. The validation of the model was done by cross validation; randomization and external test set prediction. The binding pattern of most active compound B15 was postulated based on the pharmacophoric features to further exploration of QSAR model Keywords: QSAR; MCH1 receptor; Obesity; Aminoquinline. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2126 J. Sci. Res. 1 (3), 594-605 (2009)